Przekład wulgaryzmów z języka niemieckiego na język polski i angielski – analiza porównawcza na przykładzie serialu „Dogs of Berlin” - Monika Tobiszowska (Linguistische Treffen in Wrocław)
The translation of swearwords in audiovisual content presents a particular challenge due to cultural differences. Vulgarisms are often deeply embedded in their respective cultural and social contexts, which makes their translation into other languages difficult. This study examines the role of swearwords in the German series Dogs of Berlin, with a particular focus on their functions in film. Additionally, the translation of swearwords into Polish and English is analysed to understand how they are interpreted and adapted in the respective linguistic and cultural contexts. A key focus of the analysis lies in the role of swearwords in conveying emotional impact and character development. In many cases, these expressions serve not only as a means of communication but also as a way to intensify emotions, express social tensions, and highlight conflicts between characters. This study explores how the specific functions of swearwords in the film are altered or preserved through the translation process. The analysis reveals that the intensity of swearwords often needs to be adjusted to ensure they remain understandable and appropriate in a different cultural context. In doing so, nuances may be lost, which can affect how the series is perceived by audiences from different cultural backgrounds. The conclusions highlight that the perception of swearwords is strongly influenced by cultural and social factors, leading to varying interpretations and reactions among viewers.